2021
DOI: 10.1111/fwb.13822
|View full text |Cite
|
Sign up to set email alerts
|

Community shifts from eukaryote to cyanobacteria dominated phytoplankton: The role of mixing depth and light quality

Abstract: 1. Lake stratification strengthens with increasing surface water temperatures, thereby reducing the depth of the mixed layer. Phytoplankton communities are not only exposed to different nutrient availability within a mixed water column, but also to different light quality. We conducted controled laboratory and mesocosm experiments to investigate phytoplankton, especially cyanobacteria, responses to different light quality and mixing depths.2. Our mesocosm experiment allowed the manipulation of mixing depth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 121 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…Dinophytes were strongly and positively affected by both temperature and DEP during the stratification period June-September, the latter likely reflecting that these motile algae can migrate between a nutrient-rich layer (meta-/hypolimnion) and the surface to harvest light [40]. The stability of the stratification is higher under warmer conditions and often at a shallower depth [4,9]. Moreover, some fully mixed lakes may become temporarily or fully stratified in warm years [10], which may further stimulate both dinophyte and cyanobacteria growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinophytes were strongly and positively affected by both temperature and DEP during the stratification period June-September, the latter likely reflecting that these motile algae can migrate between a nutrient-rich layer (meta-/hypolimnion) and the surface to harvest light [40]. The stability of the stratification is higher under warmer conditions and often at a shallower depth [4,9]. Moreover, some fully mixed lakes may become temporarily or fully stratified in warm years [10], which may further stimulate both dinophyte and cyanobacteria growth.…”
Section: Discussionmentioning
confidence: 99%
“…In correspondence with this, latitudinal gradient and cross-comparative studies have shown a greater importance of cyanobacteria in warm shallow lakes compared to colder temperate shallow lakes [6,8]. Moreover, warming intensifies stratification, and the mixing depth may become shallower, favouring cyanobacteria competition [9]; in addition, shallow lakes may become stratified [10]. This development creates optimal conditions for many cyanobacteria taxa due to their high optimum growth temperature and their ability to regulate buoyancy [11].…”
Section: Introductionmentioning
confidence: 98%
“…In light of the mechanism discussed above that CyanoHABs result from the synergistic interactions between elevated nutrients and the superior functions shaped during evolution, why it is cyanobacteria, not the eukaryotic algae, that form blooms in the same eutrophic waters? In what ways are cyanobacteria better than their co-living counterparts (e.g., Chen et al 2017, Stockenreiter et al 2021)? This question is so important such that the population-centric mechanism of CyanoHABs must be amended to accommodate the community-level dominance.…”
Section: The General Mechanism Of Cyanohabsmentioning
confidence: 99%
“…Based on this theory, some models have been developed to predict algal blooms (Wan et al 2013;Kim et al, 2021). In deep waters, water stratification was considered as an important factor affecting algal blooms (Cantin et al, 2011;Ouellet and Beisner., 2014;Ptacnik et al, 2016); light intensity was also suggested as an important factor; Zm/Ze can combine water stratification and light (Reynolds et al,1983;Diehl et al 2002;Stockenreiter et al, 2021). At present, most studies have focused on breaking the thermal stratification to control algal blooms (Visser et al, 2016;Saros et al, 2016).…”
Section: Introductionmentioning
confidence: 99%